Winifred Lamb : Aegean prehistorian and museum curator - Gill, David W. J. (Archaeopress Publishing Ltd, 2018)
A comprehensive biography of pioneering archaeologist and museum curator Winnifred Lamb, who was honorary keeper of Greek antiquities at the Fitzwilliam Museum, Cambridge in the four decades immediately following the First World War.